ANALISIS KESTABILAN LOKAL DAN BIFURKASI PADA MODEL EPIDEMI SEIV DENGAN VAKSINASI DAN PENULARAN PENYAKIT SECARA VERTIKAL - , GUNAWAN, Dr. Lina Aryati, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this Thesis, an SEIV epidemic model with vaccination, horizontal and vertical transmission, and nonlinear incidence rate is formulated. Local stability and bifurcation analysis in this model is presented in terms of the basic reproduction number R0. This model exhibits a backward bifurcation possibility, that is, the appearance of two endemic equilibria although the basic reproduction number R0 is less than the threshold 1. A locally asymptotically stable disease-free equilibrium coexists with a locally asymptotically stable endemic equilibrium for a certain condition of R0. Numerical simulation is given to illustrate the results.